ANALISIS PENGAWASAN, DISIPLIN KERJA DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI PADA DINAS KEBERSIHAN DAN PERTAMANAN KOTA MEDAN - Rizki Aulia; Husni Muharram Ritongga; Suwarno Suwarno (Ensiklopedia Education Review, 2021)
This study was conducted to explain the partial or simultaneous influence of the variables of supervision, work discipline, and work characteristics on the performance of employees at the Department of Hygiene and Parks in Medan. The total population used was 66 respondents, employees who work in the Department of Hygiene and Parks in Medan City, which were taken using a questionnaire as a method of collecting data in this study. This study uses multiple linear regression analysis. The results of the analysis show that there is a simultaneous significant effect between the three variables, and a partially significant influence between the variables of supervision, work discipline, and work characteristics on the performance of employees at the Department of Hygiene and Parks in the City of Meda.Keywords: Supervision, Work Discipline, Job Characteristics, Performance.